Comparative genomic hybridization in the investigation of myeloid leukemias - Bentz, Martin; Döhner, Hartmut; Huck, Karin; Klein, Barbara; Ganser, Arnold; Joos, Stefan; Du Manoir, Stanislas; Lichter, Peter (Genes, chromosomes & cancer, 1995)
Comparative genomic hybridization (CGH) was used for the examination of ten cases of myeloid leukemia (eight acute myeloid leukemias and two myelodysplastic syndromes). In five cases, genomic gains or losses were identified, which mapped to chromosomal regions known to be involved in this group of malignancies. In comparison to the results obtained by banding analysis, discrepancies were found in three of the ten cases; in two cases, chromosomal imbalances were not identified by CGH because they were present only in small subclones. In the other case, there were no evaluable metaphase cells for banding analysis; CGH revealed an overrepresentation of chromosome 8, which was confirmed by interphase cytogenetics with a chromosome 8-specific alphoid probe. All abnormalities revealed by CGH were confirmed by G-banding or subsequent interphase cytogenetic analysis, which demonstrates the high specificity of the method. Furthermore, in all cases, CGH identified the chromosomal imbalances present in the major clone as detected by banding analysis. The good correlation between CGH and chromosome banding results in myeloid leukemias makes this tumor a good model for the assessment of tools that are developed for automated and quantitative CGH analysis.
Gesehen am 06.11.2024